Leptin and resistin levels in serum of patients with hematologic malignancies: correlation with clinical characteristic - Pamuk, G.E.; Demir, M.; Harmandar, F.; Yesil, Y.; Turgut, B.; Vural, Ö. (Experimental Oncology, 2006)
Aim:To evaluate leptin and resistin levels in patients with various hematologic malignancies. Methods: We included 21 patients with lymphoma, 14 with multiple myeloma (MM), 14 with acute leukemia, 13 with chronic lymphocytic leukemia (CLL), and 25 healthy control subjects into our study. The subjects’ body mass indexes (BMI) were calculated; hematological and acute phase response parameters, serum lipid were determined; serum leptin and resistin levels were determined by ELISA. Results: Serum leptin level was significantly increased in CLL and MM groups when compared to the control group (p < 0.01). Resistin level was significantly higher in lymphoma patients than in CLL, acute leukemia and control groups (p < 0.01). In the control group, leptin level was negatively correlated with hemoglobin level (r = –0.44, p = 0.047); and in all patients with hematologic malignancies, leptin level was correlated with BMI (r = 0.32, p = 0.02). Leptin in lymphoma subjects correlated with hemoglobin level (r = 0.64, p = 0.005), resistin level correlated with the platelet count in patients with hematologic malignancies (r = 0.26, p = 0.044). In addition, leptin level had negative correlations with international prognostic score (IPS) in Hodgkin lymphoma (r = –0.9, p = 0.002) and with international prognostic index (IPI) in non-Hodgkin lymphoma (r = –0.77, p = 0.03). In CLL patients, leptin level had a correlation with the poor prognostic marker — CD38 level (r = 0.68, p = 0.03). Conclusion: We found higher leptin levels in MM and CLL patients, and higher resistin levels in lymphoma patients: this fact demonstrates that changes in adipose tissue and metabolism occur in these disease states. Цель: определить уровни содержания лептина и резистина в сыворотке крови больных с различными онкогематологическими заболеваниями. Методы: обследован 21 больной лимфомой, 14 — множественной миеломой (ММ), 14 — острой лейкемией, 13 — хронической лимфоцитарной лейкемией (ХЛЛ), и 25 здоровых доноров. У пациентов определены такие характеристики: индекс массы тела (ИМТ), гематологические параметры, содержание липидов в сыворотке крови. Содержание лептина и резистина в сыворотке крови определяли иммуноферментным методом. Результаты: уровень лептина в сыворотке крови был значительно выше у больных с ХЛЛ и ММ, чем таковой у контрольной группы (р < 0,01). Уровень резистина был значительно выше в группе больных с лимфомами по сравнению с ХЛЛ, острой лейкемией и контрольной группами (р < 0,01). В контрольной группе уровень лептина отрицательно коррелировал с уровнем гемоглобина (r = –0,44, р = 0,047), а во всех группах больных уровень лептина коррелировал с ИМТ (r = 0,32, р = 0,02). Уровень лептина при лимфомах коррелировал с уровнем гемоглобина (r = 0,64, р = 0,005), уровень резистина коррелировал с количеством тромбоцитов у больных всех групп (r = 0,26, р = 0,044). При лимфоме Ходжкина выявлена отрицательная корреляция между уровнем лептина и величиной международной прогностической шкалы (r = -0,9, р = 0,002), при неходжкинской лимфоме — величиной международного прогностического индекса (r = –0,77, р = 0,03), у больных ХЛЛ — с уровнем экспрессии CD38 (r = 0,68, р = 0,03). Выводы: у больных ММ и ХЛЛ выявлен высокий уровень лептина, а с лимфомами — высокий уровень резистина: этот факт указывает на то, что у больных указанными онкогематологическими заболеваниями могут возникать изменения в структуре жировой ткани и обмене веществ.